2021
DOI: 10.1088/1742-6596/1806/1/012072
|View full text |Cite
|
Sign up to set email alerts
|

Hawthorne effect and mathematical software based learning: a meta-analysis study

Abstract: The use of mathematical software in learning has been widely applied. This meta-analysis study was conducted to examine the “Hawthorne effect”, or the novelty of using mathematical software in learning. Related databases are sought for studies that qualify for examining the effects of using mathematical software compared to traditional teaching on students’ mathematical abilities. Random-effect models with 95% confidence intervals (CIs) were estimated. 40 effect sizes were analyzed from 40 primary studies that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The research method uses a meta-analysis to combine a group of individual studies to integrate the findings [26], [27], [28], [29]. This research begins by determining the inclusion criteria, collecting and coding variables, and statistical analysis [30], [31].…”
Section: Methodsmentioning
confidence: 99%
“…The research method uses a meta-analysis to combine a group of individual studies to integrate the findings [26], [27], [28], [29]. This research begins by determining the inclusion criteria, collecting and coding variables, and statistical analysis [30], [31].…”
Section: Methodsmentioning
confidence: 99%
“…The effect size does not match the actual effect size (Frianti., 2019) and affects the meta-analysis study's quality and accuracy. Publication bias is considered to occur when the published research literature is not systematically representative of the research population carried out in the field (Tamur et al, 2021). This research used a funnel plot by Hedges's g and safe N files for publication bias testing (Garzón & Acevedo, 2019;Ulum, 2021).…”
Section: Publication Bias Analysismentioning
confidence: 99%
“…These results suggest that GILVLA implementation may be affected by the Hawthorne effect. In comparison, Tamur, Kusumah, et al (2021) has reported the effect of Hawthorne on the use of software in learning. Although the use of software has a major effect on students' learning outcomes, if it is given continuously, the effect will decrease.…”
Section: Discussionmentioning
confidence: 99%